Vita Sexualis : Karl Ulrichs and the Origins of Sexual Science - Leck, Ralph Matthew, 1961- (Book collections on Project MUSE., 2016)
Karl Ulrichs's studies of sexual diversity galvanized the burgeoning field of sexual science in the nineteenth century. But in the years since, his groundbreaking activism has overshadowed his scholarly achievements. Ulrichs publicly defied Prussian law to agitate for gay equality and marriage, and founded the world's first organization dedicated to the legal and social emancipation of homosexuals. Ralph M. Leck returns Ulrichs to his place as the inventor of the science of sexual heterogeneity. Leck's analysis situates sexual science in a context that includes politcs, aesthetics, the languages of science, and the ethics of gender. Although he was the greatest nineteenth-century scholar os sexual heterogeneity, Ulrichs retained certain traditional conjectures about gender. Leck recognizes these subtleties and employs the analytical concepts of modernist vita sexualis and traditional psychopathia sexualis to articulate philosophical and cultural differences among sexologists. Original and audacious, Vita Sexualis uses a bedrock figure's scientific and politcal innovations to open new insights into the history of sexual science, legal systems, and Western amatory codes. -- from back cover.